Enhanced Activity and Stability of Gold/Ceria-Titania for the Low-Temperature Water-Gas Shift Reaction - Carter, James H.; Shah, Parag M.; Nowicka, Ewa; Freakley, Simon J.; Morgan, David J.; Golunski, Stan; Hutchings, Graham J. (Frontiers in Chemistry, 2019)
Gold supported on ceria-zirconia is one of the most active low temperature water-gas shift catalysts reported to date but rapid deactivation occurs under reaction conditions. In this study, ceria-titania was evaluated as an alternative catalyst support. Materials of different Ce:Ti compositions were synthesized using a sol-gel methodology and gold was supported onto these using a deposition-precipitation method. They were then investigated as catalysts for the low-temperature water-gas shift reaction. Au/Ce0.2Ti0.8O2 exhibited superior activity and stability to a highly active, previously reported gold catalyst supported on ceria-zirconia. High activity and stability was found to be related to the support comprising a high number of oxygen defect sites and a high specific surface area. These properties were conducive to forming a highly active catalyst with well-dispersed Au species.